Effects of Optimism on Work Satisfaction Among Nurses: A Mediation Model Through Work-Family Conflict - Zhang, Weiyu; Zheng, Zhen; Pylypchuk, Romana; Zhao, Jinfeng; Sznajder, Kristin K.; Cui, Can; Yang, Xiaoshi (Frontiers in Psychiatry, 2021)
Background: Nurses are suffering from various stressors which adversely impact their work satisfaction and mental health. Research is scarce on optimism, one of the positive psychological resource which may reduce work-family conflict and improve work satisfaction. Objectives: This study aims to assess work satisfaction among Chinese nurses and to observe and illustrate the relationships among optimism, work-family conflict, and work satisfaction. Methods: This study was designed as a cross-sectional study with stratified sampling. From September 2019 to December 2020, a self-administered WeChat questionnaire was collected from 768 nurses online in China to evaluate the nurses' work satisfaction, optimism, and work-family conflict. Spearman correlation and hierarchical multiple regression analysis were applied to examine associated factors of work satisfaction. A structural equation model was employed to test the mediating effect of work-family conflict in the relationship between optimism and work satisfaction. Results: Optimism were observed to have a positive correlation with work satisfaction while the correlation between work-family conflict and work satisfaction was observed to be negative. Optimism and work-family conflict explained 4.8 and 9.2% of the incremental variances of work satisfaction, respectively. Work-family conflict served as a mediator in the relationship between optimism and work satisfaction. Conclusions: Nurses in China experienced high levels of work satisfaction. Optimism could increase the chance of higher work satisfaction while work-family conflict increased the risk of lower work satisfaction. Psychological interventions and improvement of working conditions are essential to relieve work-family conflicts and enhance work satisfaction.